Research and Application of Open-Off Cut Roof Cutting Pressure Releasing Technology - Xingen Ma; Manchao He; Weidong Li; Yilong Wang; Lifeng Li; Xiaohu Sun; Yongyuan Li; Leiyu Gu; Xingfeng Sha (Advances in Civil Engineering)
The first weighting control is one of the difficult problems that cannot be avoided in the safe and efficient production of longwall mining face. To optimize the existing pressure releasing technology of open-off cut, the open-off cut roof cutting pressure releasing (OCRCPR) technology is put forward on the basis of roof cutting pressure releasing gob-side entry retaining (RCPRGER) technology. Firstly, the mechanism of the technology and the design method of related key parameters are summarized. Then the pressure releasing effect of OCRCPR and the stress environment change under this technology are analyzed by mechanics calculation and numerical simulation, respectively, which verify the feasibility of the OCRCPR technology from the theoretical level. Finally, a test mining face is taken as an example to implement the field test. The field test results show that the OCRCPR can effectively shorten the first weighting step and weaken the first weighting strength and has a good pressure releasing effect.